The Impact of Psychological Stress and Perceived Social Support on Life Satisfaction in Parents of Children with Chronic Diseases [In Arabic] - Dellal, Samia (Milev Journal of Research and Studies, 2022)
The present research study aims to examine a hypothetical model that predicts the effect of the relationship between psychological stress and perceived social support on life satisfaction among parents of children with chronic diseases, while adopting the analytical approach to study the course of relationships. The sample consisted of 305 mothers and fathers of children with chronic diseases, who completed the psychological stress questionnaire, the perceived social support scale and the life satisfaction scale. In general, fit indices supported the hypothesized model, The results also indicated that the high level of psychological stress among the respondents directly affects life satisfaction and is negatively associated with the dimensions of perceived social support (family, friends and other distinguished people), which in turn affect life satisfactionin positive and direct manner.